Play and its Salience in Children (Kerala Journal of Psychiatry, 2024)
Play ensures the holistic development of a child across all developmental domains, provides valuable learning opportunities, enables children to practice and strengthen their skill repertoire, and provides a sense of agency to children. Play is an important medium to initiate and maintain peer relationships. Play allows children to express their feelings and allows them to work with unacceptable feelings. Article 31 of the United Nations Rights of the Child mentions that play is the right of all children. This editorial focuses on the importance of play in the life of childern.
Keywords: UNCRC Article 31; Right to Play; Play Therapy